A COMPARATIVE ANALYSIS OF DEMOCRATIC SYSTEMS: INDONESIA AND ENGLAND. - Ramadhani, Salmaa Al Zahra; Taufiqi, Muhammad Muammar (Universitas Islam kadiri, 2024)
The democratic system basically realises balance and justice for the entire community or people without any discrimination. One of its implementations is the process in general elections conducted every five years to elect executives and legislatures. There is something wrong with the implementation of this democratic system from the process and even the rules used, this research wants to discuss the constitutional system in the democratic process that is wrong or just the way the process is taken. This research is expected to be an evaluation of the Indonesian State towards the electoral system used. Normative juridical research by analysing a regulation that is directly related to legal issues. The result of this research is that Indonesia can adopt the party system and election system from the United Kingdom because it uses a two-party party system that only has two parties, namely the winner and the opposition and a district election system that only nominates one candidate from one party for one region.